My sister the supermodel - Stine, Megan; Copyright Paperback Collection (Library of Congress) (New York : HarperEntertainment, 1999)
Mary-Kate and Ashley vie for a modeling job for Real Teen magazine.
"A Parachute Press book."
"Based on the hit ABC TV series, starring Mary-Kate & Ashley!"--cover.
Keywords: Twins; Twins